2018
DOI: 10.3389/fnagi.2018.00074
|View full text |Cite
|
Sign up to set email alerts
|

Brain Aging and APOE ε4 Interact to Reveal Potential Neuronal Compensation in Healthy Older Adults

Abstract: Compensation implies the recruitment of additional neuronal resources to prevent the detrimental effect of age-related neuronal decline on cognition. Recently suggested statistical models comprise behavioral performance, brain activation, and measures related to aging- or disease-specific pathological burden to characterize compensation. Higher chronological age as well as the APOE ε4 allele are risk factors for Alzheimer's disease. A more biological approach to characterize aging compared with chronological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Furthermore, differential diagnosis between SDB‐related and age‐related brain atrophy is difficult in single‐point observational studies, particularly in those cases in which groups are matched by age and cognitive status. Thirdly, this could also be a sign of a) survival bias, as most patients with SDB may have transitioned to AD and only those with very low cortical atrophy or high in cognitive reserve at disease onset would remain as HC or MCI at cross‐section; or b) selection bias due to matching by the APOE4 allele, as it has been reported that the APOE4 allele interacts with brain aging scores measured by the BrainAGE method, revealing potential neuronal compensation in healthy APOE4+ adults (Scheller et al, ), which could also result in null findings. Fourthly, we did not account for other comorbidities and possible confounders alongside age or presence of the APOE4 allele in the prediction models (Gozal, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differential diagnosis between SDB‐related and age‐related brain atrophy is difficult in single‐point observational studies, particularly in those cases in which groups are matched by age and cognitive status. Thirdly, this could also be a sign of a) survival bias, as most patients with SDB may have transitioned to AD and only those with very low cortical atrophy or high in cognitive reserve at disease onset would remain as HC or MCI at cross‐section; or b) selection bias due to matching by the APOE4 allele, as it has been reported that the APOE4 allele interacts with brain aging scores measured by the BrainAGE method, revealing potential neuronal compensation in healthy APOE4+ adults (Scheller et al, ), which could also result in null findings. Fourthly, we did not account for other comorbidities and possible confounders alongside age or presence of the APOE4 allele in the prediction models (Gozal, ).…”
Section: Discussionmentioning
confidence: 99%
“…To simultaneously test these complex relationships, Hayes (2017, pp. 331-339) developed process macro Model 3 that has been gaining increasing popularity in other fields, such as social sciences, health science and psychology (Venta et al , 2017; Scheller et al , 2018; Backhaus et al , 2019; Gil de Zuniga et al , 2018).…”
Section: Methodsmentioning
confidence: 99%
“…While the brain may be able to adapt to perimenopausal changes in estrogen receptor networks [166], these processes may also give rise to neurological symptoms, such as cognitive dysfunction [37], particularly in women with lower capacity for neuroplastic adaptation [167].…”
Section: Neural Adaptationsmentioning
confidence: 99%